FENOLOGI GALUR-GALUR HASIL PERSILANGAN PADI RAWA LOKAL BENGKULU PADA EKOSISTEM RAWA LEBAK DANGKAL - Widodo; Usi Purwati; Sumardi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Different growing environments will have different effects on plant growth and development. The phenology of a line or variety needs to be precisely understood so that crop production management can be carried out appropriately. This study aims to evaluate the phenology of lines resulting from crossbreeding of local swamp rice from Bengkulu. The study was conducted from February 2023 to September 2023 in shallow swamp land, Faculty of Agriculture, University of Bengkulu. Using a Randomized Complete Block Design with 3 replications to place the lines UBPR-2, UBPR-3, UBPR-4, UBPR-6, UBPR-8, UBPR-9, UBPR-10 and UBPR-11. The results showed that the eight swamp rice lines evaluated had diverse phenologies. Critical stages such as tillering were grouped into 5 clusters, flowering into 6 clusters, and harvesting into 6 clusters. UBPR-2, UBPR-9, and UBPR-11 produced comparable grain weights per hill, despite varying harvest stages.